Knowledge, Attitude And Practice Of Emergency Contraceptive Usage Among Women Attending Phcs In Saudi Arabia 2021: A Cross-Sectional Study - Alhawaj, Dr. Fatimah; Alhawaj, Dr. Hanan; Alshehri, Dr. Sara; Alwagdani, Dr. Lojain (Migration Letters, 2023)
Background: Emergency contraceptive methods have proven efficacy in preventing pregnancies when administered shortly after unprotected intercourse. However, proper use is a key for efficacy. This study aimed to evaluate the level of knowledge, attitude, and practice of emergency contraceptive usage among childbearing women attending PHCs in Dammam and Khobar, Saudi Arabia. Methods: This is a cross-sectional study that included married women in childbearing period who were attending primary healthcare centers in Dammam and Khobar. A multistage random sampling technique was used and a total 460 women was included in this study. Data was collected using a predesigned questionnaire. Results: The majority of the studied sample (95.7%) had poor knowledge, and 31.7% had positive attitude with average attitude score 53.7±31.5. Among participants, only 25.8% reported having used EC before and 21.7 % reported that EC was effective. EC knowledge was significantly associated with educational level (p=0.001), family income per month (p=0.021), and number of offspring (p=0.007). Attitude was significantly associated with educational level (p=0.000), occupation (p=0.000), family income per month (p=0.000), number of offspring (p=0.001), and medical comorbidities (p=0.001). There was a significant association between attitude and having used EC before (p=0.000) and whether it was effective (p=0.000). Negative attitude was more prevalent among those who had not used EC before (p=0.000). Conclusion: The findings of the present study reveal very low levels of knowledge, higher negative attitude and low percentage of emergency contraception usage among married women. The major barriers identified were medical concerns of women and difficult accessibility. Poor knowledge was most prevalent among undergraduates, those with higher income, and those with three or more children. Negative attitude was more prevalent among undergraduates, housewives, those with high income, those with three or more children, and those free of medical comorbidities.